Cross-country ski racing performance predicted by aerobic and anaerobic double poling power - Staib, J. L.; Im, J.; Caldwell, Z.; Rundell, K. W. (The Journal of Strength and Conditioning Research, 2000)
This study investigated the relationship between double poling aerobic and anaerobic power and cross-country ski race performance. Twenty top U.S. cross-country ski racers completed a treadmill running or classical skiing o2max (LB), a long-duration treadmill double-pole o2max test (DP, 850 seconds) and a short-duration double-pole power test (UBP, 200 seconds). LB o2max (L·min1) was related to the International Ski Federation System (FIS) rank in points (r = 0.52). Strong significant relationships (p < 0.05) were identified between FIS points and DP time to exhaustion (r = 0.80), DP o2peak (r = 0.74), and UBP expressed in watts r = 0.68). DP time to exhaustion was related (p < 0.05) to UBP (r = 0.48) and DP o2peak (r = 0.76) with a multiple R of 0.85. Further analysis indicated that 75% of the variance in FIS points could be accounted for by DP o2peak (ml·kg2/3·min1) and UBP, with DP o2peak exhibiting the highest beta. Athlete ranking according to FIS points revealed 2 distinct groups. No differences in LB test results were apparent between these groups; however, the successful group had significantly higher DP and UBP results (p < 0.05). These results suggest that UBP is important, but DP o2peak is a better predictor of ski performance. This may be explained by the predominantly aerobic nature of cross-country skiing (typical event duration between 25 minutes and 2 hours for men).